2022
DOI: 10.1039/d2en00426g
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reaction of toluene/NO2/O3 on α-Fe2O3 nanoparticles: the impacts of O3, light illumination, and relative humidity on the formation of N-containing organic compounds (NOC)

Abstract: Despite the heterogeneous reaction of toluene significantly affects the atmospheric environment, less attention has been paid to the effects of O3, light illumination and relative humidity on the formation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 73 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…In some previous studies, this characteristic peak was also attributed to NO 3 − or HNO 3 . 19,47–49 In addition, IC was used to quantify NO 3 − . In IC determination, we also observed the formation of NO 3 − , and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some previous studies, this characteristic peak was also attributed to NO 3 − or HNO 3 . 19,47–49 In addition, IC was used to quantify NO 3 − . In IC determination, we also observed the formation of NO 3 − , and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In some previous studies, this characteristic peak was also attributed to NO 3 − or HNO 3 . 19,[47][48][49] In addition, IC was used to quantify (from 1.58 mg L −1 to 3.03 mg L −1 ). In the presence of SO 2 , there is formation of NO 3 − (1.50 mg L −1 ) in the dark reaction, demonstrating the oxidation of NH 3 .…”
Section: Formation Of Nomentioning
confidence: 99%
“…10,16 Furthermore, its derived intermediates can, via reaction with NO x and/or NH 3 , lead to the formation of brown carbon. 10,15,17 As the most abundant basic gas existing in the atmosphere, NH 3 is mainly derived from agricultural nitrogen fertilizer use and animal husbandry emission with a global land emission of 70-92 Tg a −1 . 18,19 Due to the large emission from agriculture and animal husbandry in China, the maximum concentration of NH 3 exceeds 100 ppbv in the North China Plain.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous studies showed the important role of Fe 2 O 3 and Fe 3 O 4 in SO 2 conversion, but few of them examined the contributions of the more abundant FeOOH. 2,[16][17][18][19][20] Previous studies suggested that FeOOH widely exists in atmospheric particulate matter, especially mineral dusts. [21][22][23][24] In addition, the abundance of FeOOH is comparable to or even higher than that of hematite.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiated Fe-containing dust may present higher heterogeneous reactivity toward atmospheric trace gases due to the photocatalytic effect of the transition metal oxides therein or the photochemical effects induced by the specific dust coatings. 4,18 However, the relevant studies concerned the photocatalytic and/or photochemical impacts of the irradiated particles rather than the irradiation intensity dependence of a series of reactions. The intensity of sunlight irradiation should be emphasized by laboratory stimulations because it changes with longitude, latitude, altitude, season, and time of day.…”
Section: Introductionmentioning
confidence: 99%